The Effect of Work Engagement and Job Satisfaction and Their Impact on Employee Commitment - Solihah, Rika; Intan, Amalia Juliana Monika; Sugiarto, Yayan (PINISI Discretion Review, 2022)
The rapid business competition is a challenge for managers in running the organizations they manage. This article aims to analyze the effect of job involvement and job satisfaction on employee commitment to the organization of Bank BPR KS in Bandung. This research is based on a survey of Bank BPR KS where in recent years there has been a high turn-over. Respondents were asked to provide responses related to the factors that influence commitment, namely job involvement and job satisfaction. There were 83 employee respondents who were sampled using the slovin formula. Multiple linear regression analysis was used in this study. The results showed that the variables of job involvement and job satisfaction had a partially significant effect on employee commitment. Based on the results of the F test, it is found that the two variables have a significant effect on employee commitment simultaneously. Based on the test results, the coefficient of determination shows that the effect of the three independent variables on the dependent variable is 58%. While the remaining 42% or influenced by other variables not examined.